The Multimodal Exercises on Physical, Functional, Agility, and Perturbation for Post- ACL Reconstruction Among Athlete: Life Sciences-Sports Rehabilitation - Kaiyaperumal, Anand Babu; Subbiah, Babu; Manikavelu, Paulraj (International Journal of Life Science and Pharma Research, 2023)
The anterior cruciate ligament (ACL) is one of the key ligaments that help stabilize our knee. Anterior cruciate ligament reconstruction (ACLR) is one of the most commonly performed orthopaedic surgeries to restore joint stability. Professional athletes may aim to return to play within 6 to 9 months safely. The multimodal approach is a condition that helps prevent injury recurrence. The study aims to determine the multimodal approach for ACL rehabilitation after reconstruction and the effect on physical, functional, agility, and perturbation for sports persons. The experimental study included 30 subjects randomly allocated into two groups group A(n=15) received multimodal training exercises, and group B(n=15) received standardized ACLR protocol training exercises. The outcome measure was International Knee Documentation Committee, Berg Balance Scale, Single Hop Test, and Agility-t-Test. Statistical analysis was done using both paired and unpaired "t" tests, which showed more significant improvement in group A. This study result shows that the Multimodal exercises along with standardized ACL rehabilitation protocol Group A show effective in improving the physical, functional, agility, and perturbation activities than the standardized ACLR protocol exercise alone Group B for sports persons who underwent ACL reconstruction after four weeks of interventions.